No association between loss-of-function mutations in filaggrin and diabetes, cardiovascular disease, and all-cause mortality. - Lise Lotte N Husemoen (Public Library of Science (PLoS), 2013)
Background Common loss-of-function mutations in the filaggrin gene (FLG) are a major predisposing risk factor for atopic disease due to reduced epidermal filaggrin protein levels. We previously observed an association between these mutations and type 2 diabetes and hypothesized that an inherited impairment of skin barrier functions could facilitate low-grade inflammation and hence increase the risk of diabetes and cardiovascular disease. We examined the association between loss-of-function mutations in FLG and diabetes, stroke, ischemic heart disease (IHD), and all-cause mortality in the general population. Methods The R501X and 2282del4 loss-of function mutations in FLG were genotyped in four Danish study populations including a total of 13373 adults aged 15-77 years. Two of the studies also genotyped the R2447X mutation. By linkage to Danish national central registers we obtained information for all participants on dates of diagnoses of diabetes, stroke, and IHD, as well as all-cause mortality. Data were analyzed by Cox proportional hazard models and combined by fixed effect meta-analyses. Results In meta-analyses combining the results from the four individual studies, carriage of loss-of-function mutations in FLG was not associated with incident diabetes (hazard ratio (HR) (95% confidence intervals (CI)) = 0.95 (0.73, 1.23), stroke (HR (95% CI) = 1.27 (0.97, 1.65), ischemic heart disease (HR (95%CI) = 0.92 (0.71, 1.19), and all-cause mortality (HR (95%CI) = 1.02 (0.83, 1.25)). Similar results were obtained when including prevalent cases in logistic regression models. Conclusion Our results suggest that loss-of-function mutations in FLG are not associated with type 2 diabetes, cardiovascular disease, and all-cause mortality. However, larger studies with longer follow-up are needed to exclude any associations.